Microbiological evaluation of Ultra-High-Temperature (UHT)-treated milk close to expiry date and routine home practices for preservation of milk - Udayalaxmi Jeppu; Namitha Jayaram; Sneha Satya; Amrutha Kandathil Purayil (Wolters Kluwer Medknow Publications, 2015)
Background: As milk is an excellent medium for growth of microorganisms, milk gets contaminated very easily leading to its early spoilage and to milk-borne diseases. Objectives: To compare the quality of pasteurized milk with milk cooker-treated milk and to compare the quality of fresh ultra-high-temperature (UHT) milk with that of UHT milk close to expiry date. Materials and Methods: Samples of pasteurized milk, milk heated in milk cooker, fresh UHT milk, and UHT milk nearing expiry date were tested by methylene blue reduction test, coliform test, and colony count test. The results were analyzed statistically using Statistical Package for Social Sciences (SPSS) version 11.5. Results: All milk samples passed the methylene blue test and UHT-treated milk passed the coliform test also. Out of the 30 fresh pasteurized milk samples, seven (23.3%) passed the coliform test; but the same after milk cooker treatment, 16 (53.3%) passed the coliform test (P < 0.05). Fourteen (46.6%) out of 30 fresh pasteurized milk samples failed the colony count test, but the same after milk cooker treatment only eight (26.6%) failed the test (P = 0.583). Only seven out of the 60 UHT milk samples failed the colony count test and out of these six (20%) were close to expiry date (P < 0.05). Conclusions: Milk cooker-treated milk appears to be safer than the fresh pasteurized milk. Fresh UHT-treated milk is safer then UHT milk close to expiry date.